Hierarchical nanosheet-based Ni3S2 microspheres grown on Ni foam for high-performance all-solid-state asymmetric supercapacitors. (25th September 2017) - Li, Gaofeng; Cong, Yuan; Zhang, Chuanxiang; Tao, Haijun; Sun, Yueming; Wang, Yuqiao
Abstract: The hierarchical nanosheet-based Ni3 S2 microspheres directly grew on Ni foam using a two-step hydrothermal method. The microsphere with a diameter of ∼1 microns and a rough surface was well connected to each other without any binders to provide a larger specific surface area, shorter ion/electron diffusion paths, richer electroactive sites as a supercapacitor electrode. As a three-electrode supercapacitor, it delivers a high specific capacity of 981.8 F g −1 at 2 A g −1, an excellent rate capability of 436.4 F g −1 at 12 A g −1, and a good cycling stability of 950.9 F g −1 with 96.9% retention after 1000 cycles at 2 A g −1 . Furthermore, an asymmetric supercapacitor based on Ni3 S2 -microsphere as a positive electrode and active carbon as a negative electrode shows a high energy density of 29.4 Wh kg −1 at 324.5 W kg −1 and a high power density of 3197.6 W kg −1 at 15.1 Wh kg −1 . This work demonstrates that nanosheet-based Ni3 S2 microspheres coated Ni foam can be an effective electrode for a real supercapacitor.